Clinical-Physiological Considerations in Patients Undergoing Staged Palliation for a Functionally Single Ventricle. (August 2016) - Penny, Daniel J.; Krishnamurthy, Rajesh
Abstract : Objectives: The objectives of this review are to discuss the pathophysiology of the circulation with a functionally univentricular heart, with a focus on the unique physiologic characteristics, which provide the underpinnings for the management of these complex patients. Data Source: MEDLINE and PubMed. Conclusions: The circulation of the patient with a functionally univentricular heart displays unique physiologic characteristics, which are quite different from those of the normal biventricular circulation. There are profound differences within the heart itself in terms of ventricular function, interventricular interactions, and myocardial architecture, which are likely to have significant implications for the efficiency of ventricular ejection and metabolism. The coupling between the systemic ventricle and the aorta also displays unique features. The 3D orientation of the Fontan anastomosis itself can profoundly impact cardiac output, although the "portal" pulmonary arterial bed is a crucial determinant of overall cardiovascular function. As a result, disease-specific approaches to improve cardiovascular function are required at all stages during the care of these complex patients.